Facilitating and inhibiting factors for long-term involvement of patients at outcome conferences—lessons learnt from a decade of collaboration in OMERACT: a qualitative study - de Wit, Maarten (BMJ Publishing Group, 2013)
OBJECTIVE: Several studies have provided insights into the conditions for successful patient involvement in health research. We recently demonstrated that long-term engagement with people with rheumatic conditions in international outcome research led to significant changes in the research agenda in the field of rheumatology. This article explores facilitating and inhibiting factors for long-term involvement of patients as collaborative partners at five Outcome Measures in Rheumatology (OMERACT) conferences. DESIGN: Responsive evaluation, starting with a thematic document analysis of conference proceedings and the grey literature, followed by 38 qualitative interviews. Interview transcripts were subjected to inductive content analysis. SETTING: 5 international OMERACT conferences between 2002 and 2012. PARTICIPANTS: Patient delegates (n=16) and professional delegates representing researchers (n=14), pharmaceutical industry and regulators (n=2). RESULTS: Combined review of the document analysis and interview data revealed five main facilitators and three main barriers. Patient engagement as full participants at OMERACT conferences was enhanced by: strong leadership commitment and the presence of change agents, a clear selection procedure, an inclusive consensus-based conference design, individualised and self-organised support, an interactive and encouraging moderation style during discussion groups. Barriers were related to the intensity of the conference programme, scepticism among researchers and doubts about the representativeness of the patient group. CONCLUSIONS: This study concludes that developing a sustainable structure for funding, selection and support of patient delegates, as well as adjusting conference design and moderation style, contributes not only towards facilitating direct dialogue between all stakeholders but also towards enhancing mutual understanding and the successful incorporation of the patient perspective in an outcome conference such as OMERACT.